Biochemical Aspects of a Serine Protease from Caesalpinia echinata Lam. (Brazilwood) Seeds: A Potential Tool to Access the Mobilization of Seed Storage Proteins - Priscila Praxedes-Garcia; Ilana Cruz-Silva; Andrezza Justino Gozzo; Viviane Abreu Nunes; Ricardo José Torquato; Aparecida Sadae Tanaka; Rita de Cássia Figueiredo-Ribeiro; Yamile Gonzalez Gonzalez; Mariana da Silva Araújo (The Scientific World Journal)
Several proteins have been isolated from seeds of leguminous, but this is the first report that a protease was obtained from seeds of Caesalpinia echinata Lam., a tree belonging to the Fabaceae family. This enzyme was purified to homogeneity by hydrophobic interaction and anion exchange chromatographies and gel filtration. This 61-kDa serine protease (CeSP) hydrolyses H-D-prolyl-L-phenylalanyl-L-arginine-p-nitroanilide (Km 55.7 μM) in an optimum pH of 7.1, and this activity is effectively retained until 50∘C. CeSP remained stable in the presence of kosmotropic anions (PO4 3−, SO4 2−, and CH3COO−) or chaotropic cations (K+ and Na+). It is strongly inhibited by TLCK, a serine protease inhibitor, but not by E-64, EDTA or pepstatin A. The characteristics of the purified enzyme allowed us to classify it as a serine protease. The role of CeSP in the seeds cannot be assigned yet but is possible to infer that it is involved in the mobilization of seed storage proteins.